(untitled) (Journal of the College of Basic Education, 2023)
The table tennis game is one of the individual sports games that involves multiple interconnected offensive and defensive skills. So that if one of them is missing or the level is weak in it, it leads to losing many points during the game, especially those that are directly related to scoring points, including the different types of serve. The researchers relied on studying this problem in the light of the research hypothesis that there is a relationshipBetween serving and ranking achievement for the men’s national team table tennis players.The research hypothesis was born and verified, the researchers used statistical methods.The appropriate fit for this is the arithmetic mean, standard deviation, and Spearman’s law of ranks. The researchers concluded that there is a very strong and high correlation between the level of performance and the skill of serving and the level of achievement achieved by the players. The researchers recommended the necessity of paying attention to intensive training on the skill of the serve strike, allocating a relatively large amount of time, and diversifying the period of serving training with its various types during the training unit, and then evaluating the performance. Chapter one